Seen and unseen. - Stokes, Patrick (New Philosopher, 2025)
The article explores the complexities of observation in science, particularly in relation to astronomical phenomena and advanced imaging technologies. It contrasts the vibrant images produced by telescopes like Hubble and James Webb with the often monochrome views seen through ground-based telescopes, raising questions about what constitutes "real" observation. The discussion includes philosophical perspectives on observation, such as those by Bas van Fraassen, and highlights how scientific instruments mediate our understanding of reality, as seen in examples like fMRI and Kirlian photography. Ultimately, the article suggests that advancements in technology may redefine our concepts of observation and existence, leaving open the possibility of unobservable entities in the universe.